Green Cloud Computing (International Journal of Engineering and Computer Science, 2022)
This paper discusses the carbon footprint caused by computer resources, cloud computing and the damage it causes to nature. The growing need of data centers and the resulting environmental problems like emission of harmful gases and production of heat are a relevant field of study. Efficient use of computing resources without harming the nature on pay-as-you-go basis is a concern. This paper discusses how to improve the above with green computing.Keywords – Cloud Computing, Green Cloud Computing, Carbon Emission, Sustainable Energy, Eco-Friendly;